Limitations of a polymer-based hole transporting layer for application in planar inverted perovskite solar cells. Issue 8 (4th July 2019) - Petrović, Miloš; Maksudov, Temur; Panagiotopoulos, Apostolos; Serpetzoglou, Efthymis; Konidakis, Ioannis; Stylianakis, Minas M.; Stratakis, Emmanuel; Kymakis, Emmanuel
Abstract : Operational stability and structural integrity of a poly(triarylamine) hole transporter and methylammonium lead halide absorber are investigated upon exposure to UV stress. Abstract : Planar inverted lead halide photovoltaics demonstrate remarkable photoconversion properties when employing poly(triarylamine) (PTAA) as a hole transporting layer. Herein, we elucidate the effect of ambient ultraviolet (UV) degradation on the structural and operational stability of the PTAA hole transporter through a series of rigorous optoelectrical characterization protocols. Due attention was given to the interplay between the polymer and perovskite absorber, both within the framework of a bilayer structure and fully assembled solar cells. The obtained results imply that UV degradation exerts a major influence on the structural integrity of PTAA, rather than on the interface with the perovskite light harvester. Moreover, UV exposure induced more adverse effects on tested samples than environmental humidity and oxygen, contributing more to the overall reduction of charge extraction properties of PTAA, as well as increased defect population upon prolonged UV exposure.